Immune Mechanisms in Atherosclerosis, Especially in Diabetes Type 2 - Frostegard, Johan (Frontiers in Endocrinology, 2013)
Atherosclerosis and ensuing cardiovascular disease (CVD) are major complications of diabetes type 2. Atherosclerosis is a chronic inflammatory condition involving immunocompetent cells of different types present in the lesions. Even though inflammation and immune activation may be more pronounced in atherosclerosis in diabetes type 2, there does not appear to be any major differences between diabetics and non-diabetics. Similar factors are thus implicated in atherosclerosis-associated immune activation in both groups. The cause of immune activation is not known and different mutually non-exclusive possibilities exist. Oxidized and/or enzymatically modified forms of low density lipoprotein (OxLDL) and dead cells are present in atherosclerotic plaques. OxLDL could play a role, being proinflammatory and immunostimulatory as it activates T-cells and is cytotoxic at higher concentrations. Inflammatory phospholipids in OxLDL are implicated, with phosphorylcholine (PC) as one of the exposed antigens. Antibodies against PC (anti-PC) are anti-atherogenic in mouse studies, and anti-PC is negatively associated with development of atherosclerosis and CVD in humans. Bacteria and virus have been discussed as potential causes of immune activation, but it has been difficult to find direct evidence supporting this hypothesis, and antibiotic trials in humans have been negative or inconclusive. Heat shock proteins (HSP) could be one major target for atherogenic immune reactions. More direct causes of plaque rupture include cytokines such as interleukine 1β (IL-1ß) , tumor necrosis factor (TNF), and also lipid mediators as leukotrienes. In addition, in diabetes, hyperglycemia and oxidative stress appear to accelerate the development of atherosclerosis, one mechanism could be via promotion of immune reactions. To prove that immune reactions are causative of atherosclerosis and CVD, further studies with immune-modulatory treatments are needed.